The complete mitochondrial genome of Achatinella sowerbyana (Gastropoda: Pulmonata: Stylommatophora: Achatinellidae). Issue 1 (1st January 2016) - Price, Melissa R.; Forsman, Zac H.; Knapp, Ingrid S.; Toonen, Robert J.; Hadfield, Michael G.
Abstract: In this study, we report the complete mitochondrial genome sequence of Achatinella sowerbyana, an endangered Hawaiian tree snail. The mitogenome is 15, 374 bp in length and has a base composition of A (36.4%), T (42.7%), C (9.1%), and G (11.8%). Similar to other pulmonates, it contains 13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes. The gene order is the same as its sister species, A. mustelina . To our knowledge, this is the second mitochondrial genome sequenced within the superfamily Achatinelloidea, and will aid in the examination of the genus Achatinella, part of a spectacular radiation in the Hawaiian Islands.